2010
DOI: 10.1016/j.geomorph.2009.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Morphological barrier island changes and recovery of dunes after Hurricane Dennis, St. George Island, Florida

Abstract: During the summer of 2005, Hurricane Dennis overwashed the eastern portion of St. George Island, part of the northwest barrier island chain located along the Florida Panhandle. In this paper, LiDAR-based morphological changes of the barrier island are analyzed, along with the short-term post-storm recovery of secondary dunes. Results show that overwash from the storm surge removed nearly the entire foredune complex, and the initial breaching probably occurred where the complex was either low or discontinuous; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 26 publications
9
58
0
1
Order By: Relevance
“…Growth of the dune follows a sigmoid curve consistent with the growth models used to quantify vegetation growth (see Hugenholtz and Wolfe, 2005a,b). Specifically, the data presented in Morton et al (1994) and several survey transects from Priestas and Fagherazzi (2010) all follow the growth model of Verhulst (1838):…”
Section: Introductionmentioning
confidence: 84%
“…Growth of the dune follows a sigmoid curve consistent with the growth models used to quantify vegetation growth (see Hugenholtz and Wolfe, 2005a,b). Specifically, the data presented in Morton et al (1994) and several survey transects from Priestas and Fagherazzi (2010) all follow the growth model of Verhulst (1838):…”
Section: Introductionmentioning
confidence: 84%
“…This evaluation of the BCE curvature with BCE H helped identify the geomorphic physical processes (i.e. wave impact vs. aeolian transport) that was most actively affecting this portion of the beach, and therefore was useful in assessing beach state and recovery (Morton et al, 1994: Priestas andFagherazzi, 2010). Once calculated, we evaluated the application of these BCE metrics to quantitatively capture upper beach changes in line with beach recovery stages (Wright and Short, 1984;Morton et al, 1994).…”
Section: Linking Bce To Storm Response and Recoverymentioning
confidence: 99%
“…Zeigler et al, 1959;Lee et al, 1998;Houser et al, 2008;Castelle et al, 2015;Suanez et al, 2015) to sandy beaches (Wright and Short, 1984;Sexton and Hayes, 1991;Morton, 2002;Priestas and Fagherazzi, 2010) and dunes (Saunders andDavidson-Arnott, 1990, Hesp, 2002;Psuty et al, 2005;McLean and Shen, 2006;Houser, 2012;Plant and Stockdon, 2012;Lentz et al, 2013;Houser et al, 2015;Weymer et al, 2013;Wilson et al, 2015). These studies assess change using a variety of beach metrics including island volume, shoreline and dune position, and profile topography from consecutive elevation surveys (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Note the absence of planktonic species and Bolivina subaenariensis that are present in washover deposits but not in the modern distributions. Priestas and Fagherazzi (2010) stated that despite washover sediment being predominantly eroded from the shoreface and foredune that barrier islands do not always conserve mass following a hurricane and that a significant volume can be lost to the offshore area and back-bay. Stone et al (2004) had concluded that storms can be both 'constructive' and 'destructive' with regards to barrier island sediment budgets.…”
Section: Stratigraphy and Sedimentologymentioning
confidence: 99%